The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1968
DOI: 10.1029/jb073i018p06039
|View full text |Cite
|
Sign up to set email alerts
|

The behavior of spectral features in the infrared emission from particulate surfaces of various grain sizes

Abstract: Several inorganic materials are used to illustrate that bands in infrared emission spectra of solids change shape as the particle size of the sample is altered, and that the way in which a particular band changes depends upon the value of its absorption coefficient. The relationship found to exist between corresponding band shape changes in emission and reflection spectra indicates that Kirchoff's law holds to a first‐order approximation for particulate, or mat, surfaces. The implications of band shape changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
1

Year Published

1970
1970
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(106 citation statements)
references
References 3 publications
3
102
1
Order By: Relevance
“…Some minerals exhibit the phenomenon of reststrahlen in this spectral interval (Aronson, et al 1967;Hovis,1966;Hovis, et al 1968;Hunt and Vincent, 1968;Lyon, 1965). Laboratory measurements show a correlation of the location of the reststrahlen peaks in the spectral reflectance curves of various silicate bear ing minerals with their SiO 2 content.…”
Section: Surface Emissivity Effectsmentioning
confidence: 99%
“…Some minerals exhibit the phenomenon of reststrahlen in this spectral interval (Aronson, et al 1967;Hovis,1966;Hovis, et al 1968;Hunt and Vincent, 1968;Lyon, 1965). Laboratory measurements show a correlation of the location of the reststrahlen peaks in the spectral reflectance curves of various silicate bear ing minerals with their SiO 2 content.…”
Section: Surface Emissivity Effectsmentioning
confidence: 99%
“…Besides, in addition to these progressive modifications, the band shapes were markedly modified in comparison with those of the single crystal but the bands shapes did not evolve significantly with the increase in porosity between 500 and 900 cm -1 . Several authors [10,[15][16][17][18][19] showed that the band shape of the spectral emissivity was dependent on the grain size and the grain shape constituting the surface of the sample. Several types of behaviors appeared according to the particle size and the value of the absorption coefficient K (e.g.…”
Section: Roughness Effect In the Opaque Zonementioning
confidence: 99%
“…Type 3 4 behavior involves an increase in spectral contrast with decreasing particle size. 10 The calcite ν3 anti-symmetric stretching mode shows type 1 behavior, whereas the [CO3 are dependent on the wavelength. The critical diameter for a transition in optical properties is related to the absorption coefficient (α) and is proportional to wavelength (λ) and (k) defined as 2,13 :…”
Section: Introductionmentioning
confidence: 99%